2011
DOI: 10.1021/ef200745x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Coal Type and Particle Size on Char–CO2 Gasification via Gas Analysis

Abstract: Char gasification is affected by operating conditions such as reaction temperature, reactant gas partial pressure, total system pressure, and particle size, in addition to the chemical composition and the physical structure of the coal. We characterized the effects of coal type and particle size on the CO 2 gasification of chars prepared from 12 bituminous coals at different reaction temperatures (1050À1400 °C). Each coal sample was devolatilized at 950 °C in a nitrogen atmosphere to become coal char, and it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 23 publications
6
53
0
Order By: Relevance
“…As the bed temperature increases, the carbon conversion during gasification reaction increases by oxidation, Boudouard and water gas shift reaction which shows almost linear relationship. Results of Xiao et al (2006) are in good agreement with the other authors (Liu et al 2008;Kim et al 2011). Corella et al (2006) have reported that gasification temperature has both the positive effect as well as negative effect on coal gasification reaction.…”
Section: Effect Of Temperature On Coal Gasificationsupporting
confidence: 89%
See 3 more Smart Citations
“…As the bed temperature increases, the carbon conversion during gasification reaction increases by oxidation, Boudouard and water gas shift reaction which shows almost linear relationship. Results of Xiao et al (2006) are in good agreement with the other authors (Liu et al 2008;Kim et al 2011). Corella et al (2006) have reported that gasification temperature has both the positive effect as well as negative effect on coal gasification reaction.…”
Section: Effect Of Temperature On Coal Gasificationsupporting
confidence: 89%
“…In contrast to above results, Miura et al (1989) and Hurt et al (1991) have reported that the pore structure is not a factor which controls the gasification reaction rate of highly reactive char. Jenkins et al (1973), Beamish et al (1998), Messenbock et al (2000), Zhang et al (2006) and Kim et al (2011) have reported that the reactivity of coal char during gasification is dependent on volatile matter content in coal and rank of coal. Reactivity of char is directly proportional to the volatile content of coal, i.e., reactivity of char increases with increase in volatile matter content (Beamish et al 1998;Zhang et al 2006;Kim et al 2011).…”
Section: Effect Of Porosity Of Char On Coal Gasificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable amount of literature is available in which gasification of char is presented. Kim, et al [10] prepared char from 12 different bituminous coals at different reaction temperature for the gasification with CO 2 under isothermal conditions. The concentration of CO and CO 2 measured using online gas analyser.…”
mentioning
confidence: 99%